Allogeneic fibroblasts ameliorate intervertebral disc degeneration by reducing osteophytes in rabbits - Chen, Chen; Huang, Yizhuo; Shi, Lei; Zhou, Li; Zhou, Shenao; Wan, Hongjin; Yang, Xiao; Zhao, Jie (Frontiers in Medicine, 2024)
Low back pain (LBP) was commonly induced by intervertebral disc degeneration (IVDD), which is accompanied by the loss of disc height and osteophyte generation. Cell-based therapy is a promising treatment for preventing the degeneration of interverbal disc. Here, we established a rabbits-derived fibroblast (Rab-Fib) which could be expanded in vitro. On puncture induced intervertebral disc degeneration (IVDD) rat models, Rab-Fib had significant therapeutic effects as X-ray, CT and MRI results indicated an exceptional mitigation of disc degeneration. Therefore, this study could be a foundation of further applying fibroblast into clinical trials.